Pemerolehan Kosakata Anak Usia Lima Tahun di Nagari Bukik Batabuah - Iska, Yulia; Ngusman, Ngusman; Tressyalina, Tressyalina (Universitas Negeri Padang, 2012)
The purposes of this study were to (1) describe the kinds of words aquisition by childrens 5 years old at Bukik Batabuah, (2) describe the kinds of meanings aquisition by childrens 5 years old at Bukik Batabuah, (3) describe the words by semantic field which is aquisition by childrens 5 years old at Bukik Batabuah, and (4) describe the step of semantic aquisition chidren 5 years old at Bukik Batabuah. The data of this study were speech acts the children 5 years old at Bukik Batabuah. Data were colected by using observation method, interview technique, record technique, and note technique. The findings of this study showed that the children 5 years old at Bukik Batabuah (1) has aquisition 12 kinds of words, they are, verb, noun, adjektive, adverbial, pronominal, demonstrative, interogative, numeral, preposition, articula, interjection, and fatic categorial, (2) has aqusition 9 kinds of means, they are leksical, grammatical, referencial, nonreferencial, denotative, conotative, figure, idiomatic, and word meaning, (3) aquisition the most word in the activity semantic field, and (4) childen were not in the generalisation step in semantic aquisition’s step, but they are going to that step.